“Happy to provide the knives”: Governmentality and threats of violence via social media in the case of Roosh V and Return of Kings - Bender, Stuart (University of Illinois, 2017)
This paper uses the online threats of violence to Roosh V and Return of Kings — blogs relating to pick-up artist culture and “neo-masculinity” — as a case study to examine the ways in which people use social media as a technology of the self. In early 2016, groups mobilized online using the Facebook platform to protest meet-ups that had been planned by Roosh V for his supporters. Some of the Facebook users responded with extreme suggestions to rape Roosh and the Return of Kings members themselves, violating them with sharp objects, as well as outright murder. In this paper I am interested in a specific question related to governmentality: what do these hateful, violent threats suggest about the way people use social media as a form of self-governance?